Changes in Blood Pressure Level With Aging and Factors Which Affected Blood Pressure Level and Its Association with Women Health - Rana, Mahima; Bisla, Gita (Asian Journal of Science and Applied Technology, 2018)
The aim of the present study was to examine changes in blood pressure among an adult woman with age. Hypertension is a major contributor to morbidity and mortality worldwide and is widespread in older women. Hypertension is one of the major risk factors associated with cardiovascular disease and is also a component of the metabolic syndrome. A total of 2,000 women classified in four age groups were examined: 20-30, 31-40, 41-50 and 51-60 years. Blood pressure was measured with a sphygmomanometer and a stethoscope (either electronically or directly into the arteries). In this study, we found that hypertension is a more common problem in women with increasing age. It affects all age groups, but the most vulnerable group was between 51 and 60 years old.